STATUS OF COMPREHENSIVE REHABILITATION ORGANIZATION FOR PATIENTS WITH DENTAL ARCH DEFECTS: SPECIALISTS' PERSPECTIVES - R.V. Tsynkush (Український стоматологічний альманах)
Despite the implementation of modern diagnostic methods, treatment approaches, and preventive measures, the prevalence of dental arch defects remains significant in the adult population of Ukraine. Exploring specialists' opinions can contribute to improving dental services, enhancing the performance of medical institutions, and refining professionals' skills.